A plane boundary value problem of Thermo- magnetoelasticity for two parallel DC-bus bars by a boundary integral method - Eldhaba, Amr Ramadan (JOURNAL OF ADVANCES IN MATHEMATICS, 2014)
A boundary integral method previously introduced by two of the authors [1] is properly extended to investigate the plane problem of linear, uncoupled thermo-magnetoelasticity for two parallel, infinite, circular cylindrical electric conductors carrying steady, axial currents and placed a distance apart in an external medium kept at a constant temperature. Such a setting allows disregarding the thermal interaction between the two cylinders, leaving only the magnetic interaction. The basic equations and boundary conditions are briefly mentioned as in [1] and the solution of the problem is obtained for all quantities of physical interest. Numerical results are given for the so-called magnetic displacements occurring in the representation of the mechanical displacements and a detailed discussion of these results is provided.